COGNITIVE MORAL APPROACH TO CIVICS EDUCATION MATERIAL DEVELOPMENT IN THE ELEMENTARY SCHOOL - Yogi Prihandoko; St. Y. Slamet; Winarno Winarno (Jurnal Kependidikan, 2017)
PENDEKATAN COGNITIVE MORAL SEBAGAI KERANGKA PENGEMBANGAN BAHAN AJAR PPKN DI SEKOLAH DASARAbstrakPenelitian ini bertujuan untuk mendeskripsikan implementasi pembelajaran PPKn sebagai wahana pendidikan moral dan relevansi pendekatan cognitive moral sebagai kerangka pengembangan bahan ajar PPKn untuk membelajarkan nilai-nilai moral. Penelitian ini adalah deskriptif analitis dengan menggunakan pendekatan kualitatif. Subjek penelitian adalah 122 siswa kelas V sekolah dasar dan 4 guru pengampu Mata Pelajaran PPKn pada empat kecamatan di Kota Salatiga. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, angket, wawancara, dan studi dokumen. Temuan hasil penelitian dianalisis menggunakan analisis interaktif model Miles dan Huberman kemudian disajikan melalui teks narasi deskriptif. Hasil penelitian menunjukkan bahwa pertama, proses pelaksanaan pembelajaran PPKn belum merepresentasikan pendidikan moral. Kedua, guru tidak melaksanakan pembelajaran moral yang terencana dan sistematis dalam pembelajaran PPKn. Ketiga, pengetahuan siswa tentang moral rendah. Keempat, siswa mengalami miskonsepsi terhadap substansi dan tujuan PPKn. Kelima, muatan PPKn pada buku tematik Kurikulum 2013 tidak menguraikan materi tentang moral. Keenam, pendekatan cognitive moral melalui cerita dilema relevan sebagai solusi pengembangan bahan ajar PPKn untuk membelajarkan moral di sekolah dasar. Kata kunci: cognitive moral, PPKn, sekolah dasarAbstractThe study was aimed at describing the implementation of the civics education subject as a means of moral education and the relevance of cognitive moral approach as a framework for developingcivics education instructional materials. The study was descriptive analytical research using a qualitative approach. The subjects of the study were 122 fourth-grade students of elementary school and 4 teachers of civics education in four districts in Salatiga City. The data collection techniques were observation, questionnaires, interviews, and documents. The data were analyzed using interactive analysis of Miles and Huberman model and presented through descriptive narrative texts. The results show that first, civic education learning has not yet represented moral education. Second, teachers do not carry out planned and systematic moral learning in civics education learning. Third, students’ moral comprehension is still low. Fourth, students have misconceptions about the substance and the purpose of civics educationlearning. Fifth, the content of civics education in the thematic book of Curriculum 2013 does not include the material related to moral learning. Sixth, the cognitive moral approach through the dilemma story is relevant as a solution for the development of civics education instructional materials to teach morals in the elementary school.Keywords:cognitive moral, civic education, elementary school education